Pengaruh Pertumbuhan Bibit Kelapa Sawit (Elaeiguineensis Jacq) Pada Media Tanah Ultisol Dengan Pemberian Mikoriza dan Pupuk NPK Di Pembibitan Utama - Nurliana Pulungan; Syahriandi Akbari (Universitas Batanghari, 2026)
This research aims to determine the influence of interactions between mycorrhiza and NPK fertilizer. This research was carried out in the experimental garden of the Jambi University Faculty of Agriculture from August 2025 to October 2025. This research was carried out using a Randomized Group Design (RAK) with a factorial pattern of two factors and each combination was repeated 3 times. The first factor is NPK fertilizer with three doses of 10 g 6.7 g 1.8 g. and the recommendation is 10 g, while the second factor is biological fertilizer with three doses, namely 10 g 6.7 g 3.4 g. and recommendation 10 g. The observed variables were seedling height increase, leaf number increase, stem diameter increase, rachis length, and leaf area. The results of the study showed that the combination of mycorrhizal and NPK fertilizer doses could improve the growth of oil palm seedlings in the main nursery. The combination of 10 g of mycorrhizal biofertilizer + 10 g of NPK fertilizer provided the best growth compared to without the combination of mycorrhizal and NPK fertilizer. The provision of 10 g of mycorrhizal + 10 g of NPK provided the highest results in the parameters of plant height, number of leaves, and leaf area.